2012
DOI: 10.1038/cdd.2012.20
|View full text |Cite
|
Sign up to set email alerts
|

STAT3 can serve as a hit in the process of malignant transformation of primary cells

Abstract: The transcription factor signal transducer and activator of transcription 3 (STAT3) acts downstream of many pro-oncogenic signals, including cytokines, growth factors and oncogenes, and is accordingly constitutively active in a wide variety of tumors that often become addicted to it. Moreover, STAT3 is a key player in mediating inflammation-driven tumorigenesis, where its aberrant continuous activation is typically triggered by local or systemic production of the pro-inflammatory cytokine IL-6. We recently sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
59
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(59 citation statements)
references
References 38 publications
0
59
0
Order By: Relevance
“…Phospho-S727 STAT3 has been shown to localize in the mitochondria, where it positively regulates the activity of complex I/II of OXPHOS (26,56). In contrast, pY-STAT3 was shown to up-regulate glycolysis in fibroblasts and STAT3-dependent cancer cell lines (57,58). Given the hypoxic nature of tumors, we investigated whether STAT3 deficiency could alter the metabolic function of TCCs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Phospho-S727 STAT3 has been shown to localize in the mitochondria, where it positively regulates the activity of complex I/II of OXPHOS (26,56). In contrast, pY-STAT3 was shown to up-regulate glycolysis in fibroblasts and STAT3-dependent cancer cell lines (57,58). Given the hypoxic nature of tumors, we investigated whether STAT3 deficiency could alter the metabolic function of TCCs.…”
Section: Discussionmentioning
confidence: 99%
“…Given that a serinephosphorylated but tyrosine-mutant form of STAT3 was unable to rescue the STAT3 knockdown phenotype in our studies, the regulation of OXPHOS activity by mSTAT3 does not seem to be at play in our models. However, work in the laboratory of Valeria Poli has shown that transcripts encoding for mitochondrial proteins belonging to OXPHOS complexes were reduced in cells expressing constitutively activated pY-STAT3, which was associated with reduced complexes IV/V activity (57,58). Adding to the complexity of the roles of STAT3 in regulating metabolism, recent work showed that nuclear STAT3 can be tyrosine-phosphorylated by the dimeric M2 isoform of pyruvate kinase (PKM2), and together, they form a transcriptional activating complex participating in a PKM2/HIF1α-positive feedback loop (61,62).…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 95% of head and neck cancers overexpress STAT3 (19). Targeted deletion of STAT3 prevented epithelial cancers in skin cells (20), and the oncogenic role of STAT3 was shown by the ability of a constitutively active mutant to transform fibroblasts in vitro (7) and initiate tumor formation in vivo (21). Increased expression of activated STAT3 has been correlated with tumor stage and poor prognosis (7).…”
Section: Discussionmentioning
confidence: 99%
“…Phosphorylated Stat3 translocates to the nucleus and activates genes involved in proliferation, survival, and mucosal defense (Bollrath et al, 2009;Pickert et al, 2009;Ernst et al, 2014). Mutations in STAT3 have been identified as susceptibility factors for inflammatory bowel disease (Bollrath et al, 2009;Anderson et al, 2011;Demaria et al, 2012), and in mice, upon DSSinduced colitis, epithelial Stat3 is required for mucosal wound healing (Pickert et al, 2009).…”
mentioning
confidence: 99%